PERSPEKTIF ISLAM DALAM KOMUNIKASI POLITIK KYAI (Studi Etnografi Pengasuh Pondok Pesantren Annuriyyah Jember Jawa Timur) - Al Mujib, Ihwan Huda (Jurnal Nomosleca, 2020)
Kyai is a very influential figure in Islamic religion. Its influence is very large in society. The influence of the kyai in almost all fields. The magnitude of this influence has made many political actors and state officials who do political communication. Kyai is a patron for political actors and state officials who are clients. This research was conducted in Jember, East Java with a qualitative ethnographic method. The research subjects were selected based on purposive sampling. The clerics who are the subjects in this study are clerics who often accept political actors and state officials. The results of the study showed that political communication by the kyai was inseparable from an Islamic perspective. Political communication conducted by the clerics face to face is inseparable from the dissemination of the yellow book in the boarding school. This proves that the life of the kyai cannot be separated from Islamic religious doctrines Keywords: Islamic Perspective, Political Communication, KyaiDOI:Â https://doi.org/10.26905/nomosleca.v6i1.4075